State and local population projections : methodology and analysis - Smith, Stanley K. (Plenum series on demographic methods and population analysis., 2002)
This book focuses on the methodology and analysis of state and local population projections. It describes the most commonly used data sources and application techniques within each of three classes of projection methods (cohort-component, trend extrapolation, and structural models) and covers the components of population growth, the formation of assumptions, the development of evaluation criteria, and the determinants of forecast accuracy. It considers the strengths and weaknesses of various projection methods, paying special attention to the unique problems of making projections for small areas, and closes with an examination of technological and methodological changes affecting the production of small-area population projections. -- Provided by publisher.